The impact of the 21-gene recurrence score (Oncotype DX) on concordance of adjuvant therapy decision making as measured by the Liverpool Systemic Therapy Adjuvant Decision Tool. (April 2019) - Olsson-Brown, Anna; Piskilidis, Pavlos; O'Hagan, Julie; Thorp, Nicky; Robson, Peter; Innes, Helen; Wong, Helen; Cicconi, Silvia; Jackson, Richard; Kiernan, Tamara; Holcombe, Christopher; O'Reilly, Susan; et al.
Abstract: Purpose: The 21-gene recurrence score (Oncotype DX) (RS) informs systemic therapy decision making in ER-positive HER2-negative early breast cancer (BC). To date no study has described the more nuanced discussions that take place regarding systemic therapy or the impact of the RS on concordance in such decision making. Here we utilized a novel decision making tool to assess the impact of the RS on decision making as well as concordance of treatment recommendations. Patients and methods: The clinicopathological information (CPI) of 50 BCs without and with the RS were presented to a panel of breast oncologists in a simulated MDT. The Liverpool Adjuvant Systemic Therapy Decision Tool (LASTDT) was developed and used to categorize treatment recommendations. Outcome measures included the impact of the RS on decisiveness and concordance in decision making and its impact on treatment recommendations. Results: Availability of the RS increased definitive decision making from 8% (4/50) to 56% (28/50) [χ 2 = 79.35, p < 0.001] and altered the LASTDT category in 68% (34/50) of cases (p < 0.001), 74% of which were to forgo chemotherapy. With knowledge of RS, universal concordance rose from 14% to 64% [K = 0.328: K = 0.729]. Conclusions: The RS improves certainty of decision making as well as concordance amongst oncologists. This provides evidence that the availability of the RS can improve consistency of decision making amongst oncologists and thus helps to ensure patients are managed consistently. This is particularly important when patients are managed in a loco-regional, multidisciplinary team manner where heterogeneous decisions can lead to disparity in care. Highlights: Explores the complex and nuanced decision making involved treatment decisions. Introduces the Liverpool Systemic Adjuvant Therapy Decision Tool to navigate treatment choices. Highlights heterogeneity of decision making in the absence of the 21-gene recurrence score (RS). Illustrated that use of the RS significantly increased concordance across oncology experts. Concluded that the RS standardises treatment recommendation promoting standardisation of care.